Broadening Translation History by Including Absences and Failures. A Failed Proposal for Translation Policy: Insights from the Walloon Congress of 1905 - Gonne, Maud (TTR)

(untitled) (Association canadienne de traductologie, 2025)
Through the study of the failed attempt at translation policy outlined at the 1905 Walloon Congress (Liège, Belgium), this article seeks to illustrate the complex and paradoxical relationship between cultural minorities and translation policies, while emphasizing the importance of including absences and failures in the history of translation. What did not happen, was not translated, or failed for various reasons can constrain the emergence of socio-cultural reality, and prove relevant in understanding what, conversely, stabilized it in a sustainable way (Marais, 2023). After analyzing the language demands made during the Walloon Congress in the areas of justice, administration, and education, this article examines the delegates’ complex interactions and notable inconsistencies with respect to their translation management, beliefs, and practices. Finally, the study adopts both a vertical and horizontal relational approach, highlighting, on the one hand, competition between minority groups in heterogeneous and diglossic contexts—in particular the Walloon and Flemish linguistic minorities—and, on the other, the threats that official multilingual regimes, like their monolingual counterparts, can pose to a nation’s multilingual ecology.